Performance and carcass quality of broiler chickens fed diets supplemented either with Biolys(R)60 or L-Lysine-HCL - Fontanillas D.; Hohler D.; Mack S.; Neme R.; Rostagno H.S. (Feed manufacturing in the Mediterranean region. Improving safety: From feed to food, 2001)
Biolys(R)60 is a new form of lysine containing a minimum of 46.8 percent L-Lysine plus other valuable nutrients. The biological efficacy of Biolys(R)60 as compared to L-Lysine-HCI was evaluated in broiler chickens. 840 day-old male broiler chickens were allotted to seven different treatment groups with increasing supplemented levels of either L-Lysine-HCI or Biolys(R)60. Weight gain, feed intake and feed conversion and breast meat yield were determined. There was no significant difference in performance and breast meat yield of broilers fed diets supplemented either with L-Lysine-HCI or Biolys(R)60. The nutritional efficacy of the lysine source Biolys(R)60 is equivalent to that of L-Lysine-HCI.
3. Conference of Feed Manufacturers of the Mediterranean, 2000/03/22-24, Reus (Spain)